Machine Learning Approach to Predict the Dengue Cases Based on Climate Factors - Nasir, Muhammad; Aldillah Wulandhari, Shobiechah; Tenrisau, Dhihram; Haris Ibrahim, Muhammad; Rahastri, Ajeng; Sa’adatar Rohmah, Nilna; Surya, Asik; Thohir, Burhanuddin; Aryani, Desfalina; Firdaus Kasim, Muhammad (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2024)
Dengue is a global health issue threatening public health, particularly in developing countries. Effective disease surveillance is critical to anticipate impending outbreaks and implement appropriate control responses. However, delays in dengue case reporting are frequent due to human resource shortfalls. Improved outbreak predictive capacity also requires additional input on vector presence and abundance, which is currently not captured in the surveillance platform. Thus, we developed a prototype AI application, “Dengue Forecasting